Ulnar finger posture effect on a pinch strength - Shota Date; Hiroshi Kurumadani; Nanako Nakamae; Yosuke Ishii; Kazuya Kurauchi; Naoki Maniwa; Naoya Goto; Toshiyuki Fukushima; Ken Hirao; Toru Sunagawa (PLoS ONE, 2025)
Upper extremity position affects maximum pinch strength; however, there is no consensus regarding the posture of the three ulnar fingers during pinch strength testing, and existing studies have different flexion or extension posture, depending on the measurement method used. This study aimed to clarify the effect of ulnar finger posture on maximum pinch strength and to verify its reliability. Thirty-three participants (19 males and 14 females) performed maximum pulp-to-pulp pinching with both dominant and non-dominant hands. Their ulnar finger posture was tested in two positions (flexion and extension). Measurements were conducted on three separate days by two examiners. Pinch strengths were compared for ulnar finger posture, hand dominance, and sex. The intraclass correlation coefficient was calculated to assess intra-rater, inter-rater and test-retest reliability. Pinch strength in the flexion posture was significantly stronger than that in the extension posture, regardless of hand dominance or sex (1.34 times greater). Intra-rater reliability was good to excellent in the flexion posture (0.89–0.92) and moderate to good in the extension posture (0.71–0.89). Inter-rater reliability was moderate for both flexion and extension postures (flexion: 0.64–0.68, extension: 0.52–0.54). Test-retest reliability was good to excellent in the flexion posture (0.83–0.91) and moderate in the extension posture (0.71–0.72). These results indicate the importance of hand therapists instructing patients to flex their ulnar fingers during testing to obtain maximum and reliable pinch strength measurements, thereby enhancing the accuracy of hand functional assessment in clinical practice.